Víbrio em camarão e na água de três fazendas de carcinicultura do Ceará - Lima, Anahy de Souza (2007)
The objective of the present study was to identify Vibrio species in cultures of Litopenaeus vannamei in Northeastern Brazil. During the rainy and dry seasons from August 2005 to October 2006 two L. vannamei culture cycles were observed on three marine shrimp farms (A, B and C) located in the estuaries of Acaraú, Coreaú and Jaguaribe. Sixty shrimp samples and 240 pond water samples were analyzed. The outcome parameters were total vibrio count (standard plate count), saccharose-positive and negative vibrio count, and vibrio species diversity in shrimp and water samples. The lowest total vibrio count found in water samples was 2.0 x 102 CFU/mL (Farms A, and C) during the rainy season and the highest was 1,42 x 108 CFU/mL (Farm B) during the rainy season. The highest total vibrio count in shrimp samples (postlarvae and hepatopancreas) was 4,5 x 108 CFU/g (Farm B) during the dry season. The lowest and highest values observed for saccharosepositive colonies in hepatopancreas were 1.00 x 102 CFU/g (Farms A, and B) during the rainy season and 4,5 x 108 CFU/g (Farm C) during the dry season. The corresponding values for saccharose-negative colonies were 0.98 x 10 CFU/g (Farm A) and 9.50 x 105 CFU/g (Farm C), both in the rainy season. Vibrio counts were always lower in samples collected during the rainy season. A total of 118 Vibrio strains were isolated from the water (n=62) and shrimp (n=56) samples collected at the three farms. Farm B had the largest number of identifiable vibrio species (11). The most frequently isolated species was Vibrio mimicus, followed by V. alginolyticus and V. tubiashii. The lowest survival rate (37.24%) during harvesting was observed for one of the ponds at Farm A during the rainy season. Neither species diversity, nor total vibrio counts, nor saccharosepositive and negative vibrio counts in hepatopancreas samples, was associated with survival rates during harvesting. However, the combination of high vibrio counts and low species diversity observed in water samples from Farm A during the rainy season may have affected survival rates negatively. The number of vibrios increases in proportion with salinity. The likelihood of a vibrio infection in a given shrimp population cannot be determined by total vibrio counts or saccharosepositive and negative counts alone.